Bio-Packaging Based on Pectin/Tragacanth Gum with Added Extracts of Cherry Waste from the Wine Industry as a New Generation of Active Films for the Food Industry - Dobrucka, Renata; Vapenka, Lukas; Szymański, Marcin; Pawlik, Mikołaj; Lasik-Kurdyś, Małgorzata; Gumienna, Małgorzata (Foods (Basel, Switzerland), 2025)
In the present paper, extracts from pomace after cherry wine production were used as biocomponents of antioxidant packages. In the study, the highest concentrations of polyphenolic compounds were obtained when a 50% ethanol solution was used as the extraction solution. The addition of extracts provided statistically significant (p < 0.05) changes in water vapor transmission for the films obtained. The WVTR results are at a very low level, as values ranging from 7.96 ± 0.33 [g/m2 d] (sample 2) to 10.95 ± 0.33 [g/m2 d] (sample 1) were obtained. The addition of extract also affected the oxygen barrier. Samples without extract addition showed an OTR value of 2.42 ± 0.23 [cm3/m2 d 0.1 MPa]. A statistically significant (p < 0.05) reduction in this parameter was affected by the addition of extract to the matrix. Oxygen barrier properties ranged from 0.50 ± 0.05 (sample 3) to 0.94 ± 0.04 (sample 1), indicating high barrier properties of the packaging material. The addition of extracts caused an increase in opacity: films 3 and 4 were characterized by the highest value of the parameter, which was, respectively: 18.14 ± 27.02 and 18.97 ± 29.83 [%]. The research carried out in this study allows us to conclude that bioactive films with high application potential have been achieved and, in addition, represent a natural and ecological alternative to the materials currently used.
Keywords: active materials; antioxidant packaging material; extracts from fruit wine pomace